2006
DOI: 10.4049/jimmunol.177.6.3972
|View full text |Cite
|
Sign up to set email alerts
|

TNF Is Important for Pathogen Control and Limits Brain Damage in Murine Cerebral Listeriosis

Abstract: Cerebral listeriosis is a life-threatening disease. However, little is known about the bacterial virulence factors responsible for the severe course of disease and the factors of the immune system contributing to the control of Listeria monocytogenes (LM) or even to the damage of the brain. To analyze the importance of the actA gene of LM, which mediates cell-to-cell spread of intracellular LM, the function of TNF in murine cerebral listeriosis was studied. C57BL/6 mice survived an intracerebral (i.c.) infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 57 publications
3
32
0
1
Order By: Relevance
“…Thus, our data provide evidence that modulation of CD8 + T cell function is a potential strategy to improve therapy against a wide range of diseases that occur in the brain. Given the proposed roles for CD8 + T cells in mediating or protecting against numerous brain-related diseases, such as viral encephalitis (58)(59)(60), toxoplasmosis (61,62), multiple sclerosis (63-65), brain tumors (29,31,66), and cerebral listeriosis (67)(68)(69), our data have implications that extend beyond ECM to other infectious diseases, cancer, and autoimmunity.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our data provide evidence that modulation of CD8 + T cell function is a potential strategy to improve therapy against a wide range of diseases that occur in the brain. Given the proposed roles for CD8 + T cells in mediating or protecting against numerous brain-related diseases, such as viral encephalitis (58)(59)(60), toxoplasmosis (61,62), multiple sclerosis (63-65), brain tumors (29,31,66), and cerebral listeriosis (67)(68)(69), our data have implications that extend beyond ECM to other infectious diseases, cancer, and autoimmunity.…”
Section: Discussionmentioning
confidence: 99%
“…We found that expression of hepatic TNF increased in an exponential manner with time after Listeria infection of adults, but a similar rise was not found in infected neonates. Previously, it has been reported that (i) newborn rats infected with Listeria monocytogenes had deficient TNF levels, (ii) pretreatment of juvenile, but not newborn rats, with exogenous TNF decreased the splenic bacterial load, (13) and (iii) TNF is important for control of murine listeriosis (14). Importantly, neonatal mice that are deficient in the TNF receptor-1 show large necrotic lesions of neutrophils and macrophages in the liver and are unable to switch to a T-cell-mediated sterilizing response (15), suggesting a crucial role for TNF in the neonatal response to listeriosis.…”
Section: Discussionmentioning
confidence: 99%
“…(interleukin-1α, IL-1α) 、神 经 生 长 因子 -β (nerve growth factor-β, NGF-β)和肿瘤坏死因子-α (tumor necrosis factor-α, TNF-α)是细胞因子中的四个成员。 它们分布在多种组织中, 可作为介质对神经系统起 重要的调节作用。研究报道, 干扰素在大鼠中枢神 经系统损伤、生长发育和生理功能中起重要作用 (Popko et al, 1997); 白介素-1 可促进星形胶质细胞 的增殖与分化, 在大鼠胚胎发育中对中枢神经系统 起重要的调节作用, 并通过作用于白介素-1 受体 (Interleukin1 receptor, IL-1R), 促进神经元合成和释 放化学递质 (Eriksson et al, 2000;Gustafson-Vickers et al, 2008); 神经生长因子在来亨鸡脊髓胚胎发育 中对其生长发育起促进作用 (Dai & Xiyang, 2009), 并与大鼠小脑皮质 Purkinje 细胞的生理功能 (Ba et al, 2006)和诱导猕猴神经样细胞的生成 (Pei & Ji, 2003)等有关; 肿瘤坏死因子可促进大鼠星形胶质 细胞分泌 NGF (Cheng & Guo, 1999), 与大鼠的神经 元的分化和神经退行性疾病 (Oldreive & Doherty, 2010)等都有重要的关系。 皖西白鹅(Western Anhui white goose)是我国 优良的中型鹅品种之一 , 属于鸟纲雁形目鸭 科 动 物 , 是 国 家 二 级 禽 类 保 护 动 物 , 并 被 确 定 为 "国家级畜禽品种资源保护"品种。研究表明, 成年皖西白鹅大脑和小脑表达促生长激素释放肽 (ghrelin), 该物质可能以自分泌/旁分泌的形式调节 中枢神经系统 (Fang et al, 2008); 间脑、中脑和脑桥 表 达 血 管 活 性 肠 肽 (vasoactise intestinal peptide, VIP), 可能与调节视觉、听觉和肌紧张的功能有关 (Jiang et al, 2004(Jiang et al, , 2005 (Sawada et al, 2007), 在大鼠 神经系统中 NGF 通过 TrkA(tyrosine kinase-receptor) 和 NTR(p75 neurotrophin receptor)两种受体调节神 经细胞的生存和凋亡 (Yoon et al, 1998)。 另有研究表 明, 胚胎期食蟹猴小脑内的 NGF 表达水平较高, P60 时则降到原水平的 1/3 (Hayashi et al, 1990)。在 胚胎期 14 到 21 周山羊小脑皮质发育过程中, NGF-β 在 Purkinje 细胞的表达随胚龄增加逐渐增强, 并对 Purkinje 细胞的生长发育起重要的营养作用 (Qing et al, 2004)。 本实验表明, NGF-β 在 E13-E19 在 Purkinje 细胞层中表达上升, E19 后表达程度随发育天数的 增加而减弱, P15 表达呈阴性。推测 E13-E19 的 Purkinje 细胞处于生长发育阶段, NGF-β 的营养作 用加强; E19 后随着 Purkinje 细胞逐渐发育成熟, NGF-β 的营养作用也逐渐减弱; P15 时 Purkinje 细胞 已经发育成熟, NGF-β 的营养作用也随之消失。 中枢神经系统内神经细胞和小胶质细胞产生 的 TNF-α 可促进 T 细胞的产生, 参与神经免疫调控 (Virna et al, 2006), 并可作为一种神经调质或共存 递质来调节中枢神经系统的功能 (Breder et al, 1993), 在促进星形胶质细胞分泌神经生长因子 (Cheng & Guo, 1999 …”
Section: 干 扰 素 -γ(Interferon-γ Ifn-γ) 、 白 介 素 -1αunclassified